2019
DOI: 10.1097/sla.0000000000002621
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection of the Primary Tumor in Women With De Novo Stage IV Breast Cancer

Abstract: Surgical resection of the primary tumor occurs in almost half of women with stage IV breast cancer alive 1 year after diagnosis, and is increasingly occurring after systemic therapy. Coordinated multidisciplinary care remains highly relevant in the setting of metastatic breast cancer, where surgical decisions should be made on an individual basis and may affect survival in select women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 21 publications
8
92
0
Order By: Relevance
“…29 Many previous works reported no survival gain from surgery with positive margins in metastatic setting. 25,30,31 However, our study presented no survival difference between women receiving mastectomy or lumpectomy, and therefore it could be speculated that many patients may obtain clear margins after lumpectomy. Similarly, Lane et al 25 reported a positive margin rate of ,20% for patients receiving lumpectomy or mastectomy based on a national database.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…29 Many previous works reported no survival gain from surgery with positive margins in metastatic setting. 25,30,31 However, our study presented no survival difference between women receiving mastectomy or lumpectomy, and therefore it could be speculated that many patients may obtain clear margins after lumpectomy. Similarly, Lane et al 25 reported a positive margin rate of ,20% for patients receiving lumpectomy or mastectomy based on a national database.…”
Section: Discussionmentioning
confidence: 52%
“…25,30,31 However, our study presented no survival difference between women receiving mastectomy or lumpectomy, and therefore it could be speculated that many patients may obtain clear margins after lumpectomy. Similarly, Lane et al 25 reported a positive margin rate of ,20% for patients receiving lumpectomy or mastectomy based on a national database. However, we cannot determine whether more aggressive surgery (simple of modified mastectomy) can provide additional benefits.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Furthermore, this survival advantage persisted in all subgroups irrespective of age, race, tumor size, nodal status, histology grade, molecular subtype, chemotherapy status, radiotherapy status or status of distant metastasis. Metastatic breast cancer is still considered as a systemic disease and local therapy would only have little impact on outcomes (Lane et al, 2019). The primary aim of treatment is to alleviate symptoms, improve the quality of life and prolong survival.…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic breast cancer is still considered as a systemic disease and local therapy would only have little impact on outcomes [19]. The primary aim of treatment is to alleviate symptoms, improve the quality of life and prolong survival.…”
Section: Discussionmentioning
confidence: 99%